Parental relationship satisfaction, symptoms of depression and anger/hostility, and the moderating role of perceived social support—a prospective cohort study in the light of the COVID-19 pandemic - Kümpfel, Josephine; Weise, Victoria; Mack, Judith T.; Garthus-Niegel, Susan (Frontiers in Psychology, 2025)
BackgroundThe challenging early parenthood time and the strains of the COVID-19 pandemic negatively affected parental mental health, whereas relationship satisfaction and perceived social support acted protective. Previous research focused on mothers, and little is known about mental health factors besides depression. This study aimed to investigate how relationship satisfaction and perceived social support affected symptoms of depression and anger/hostility in mothers and fathers in the light of the COVID-19 pandemic and whether perceived social support moderated these associations.Methodsn = 1,414 mothers and n = 885 fathers participating in the prospective cohort DREAM study completed questionnaires 14 months and 2 years postpartum. Hierarchical moderated regression analyses were conducted, controlling for the phase in the COVID-19 pandemic (before, during lockdown, during easements, afterwards) during which mental health was assessed.ResultsGreater relationship satisfaction and perceived social support 14 months postpartum predicted fewer symptoms of depression and anger/hostility 2 years postpartum. Greater perceived social support moderated the association between relationship satisfaction and paternal symptoms of anger/hostility. Mental health symptoms were not significantly associated with the COVID-19 pandemic.LimitationsLimitations concern the limited representation of the post-pandemic group and the undifferentiated measurement of social support sources.ConclusionThe importance of relationship satisfaction and perceived social support for parental mental health is highlighted. Perceived social support can enhance the protective effect relationship satisfaction has on paternal symptoms of anger/hostility. Implementing corresponding prevention and education classes could improve parental mental health.